2017
DOI: 10.14311/ppt.2017.3.234
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms Responsible for Arc Cooling in Different Gases in Turbulent Nozzle Flow

Abstract: Abstract.A high voltage gas blast circuit breaker relies on the high speed gas flow in a nozzle to remove the energy due to Ohmic heating at high current and to provide strong arc cooling during the current zero period to interrupt a fault current. The physical mechanisms that are responsible for the hugely different arc cooling capabilities of two gases (SF 6 and air) are studied in the present work and important gas material properties controlling the cooling strength identified.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 12 publications
0
1
0
Order By: Relevance
“…In the present work, a method to quantify the arc cooling ability of different gases, with SF6 and air as examples, is established. Its main novelty is the clear accountability of the role of different energy transport processes in influencing the change of arc resistance, which is a significant step forward from the work in [32] where the relative strength of each energy exchange process towards energy removal from the arc column is studied, but no link to the change of arc resistance was established.…”
Section: Contribution Of Different Processes Towards Arc Coolingmentioning
confidence: 99%
See 3 more Smart Citations
“…In the present work, a method to quantify the arc cooling ability of different gases, with SF6 and air as examples, is established. Its main novelty is the clear accountability of the role of different energy transport processes in influencing the change of arc resistance, which is a significant step forward from the work in [32] where the relative strength of each energy exchange process towards energy removal from the arc column is studied, but no link to the change of arc resistance was established.…”
Section: Contribution Of Different Processes Towards Arc Coolingmentioning
confidence: 99%
“…The approximate radiation model [36] based on the net emission coefficient (NEC) is adopted to calculate the radiative energy source of q in Table Ⅰ. NEC is defined for an isothermal sphere of hot gas with a radius of RNEC. When this concept is used for switching arcs, an equivalent RNEC needs to be defined at each axial position in the arc column [32], and this equivalent radius is called the emission radius in this work. It depends on the radial temperature profile at the axial position.…”
Section: A the Arc Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…In high voltage circuit breakers, the flows around the instance of current interruption are typically sonic or supersonic, and the nozzle shape and exhaust area are designed to take advantage of this in the interruption and post-arc phases. For example, turbulence in the layer between arc and gas flow is an important cooling mechanism in high-velocity SF6 [11] but has proven much less important in other gasses [14]. It is also shown that the formation of shock waves affects the dielectric breakdown strength [15].…”
Section: Nozzle and Contact Geometriesmentioning
confidence: 99%